(untitled) (Journal of the Bangladesh Agricultural University, 2014)
A study was conducted to examine the nutrient content and their uptake of rice as influenced by the application of humic acid (HA) and poultry manure (PM). This experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Three levels each of humic acid (0, 3 and 6 L ha-1) and poultry manure (0, 3 and 6 t ha-1) were applied. BRRI dhan39 was used as test crop. Basal doses of N, P, K and S fertilizers were applied. Both humic acid and poultry manure either singly or in combination significantly affected the contents and uptake of N, P, K, S, Ca and Mg of BRRI dhan39. The maximum content of N, P, K, S and Ca except Mg and their uptake were recorded from the treatment combination of 6 L ha-1 humic acid along with 3 t ha-1 poultry manure. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21234 J. Bangladesh Agril. Univ. 12(1): 19-24, June 2014